Whole grain cereals for the primary or secondary prevention of cardiovascular disease - Kelly,SAM; Hartley,L; Loveman,E; Colquitt,JL; Jones,HM; Al-Khudairy,L; Clar,C; Germano,R; Lunn,HR; Frost,G; Rees,K (Cochrane Database of Systematic Reviews, 2017)
BackgroundThere is evidence from observational studies that whole grains can have a beneficial effect on risk for cardiovascular disease (CVD).Earlier versions of this review found mainly short-term intervention studies. There are now longer-term randomised controlled trials(RCTs) available. This is an update and expansion of the original review conducted in 2007.ObjectivesThe aim of this systematic review was to assess the effect of whole grain foods or diets on total mortality, cardiovascular events, andcardiovascular risk factors (blood lipids, blood pressure) in healthy people or people who have established cardiovascular disease orrelated risk factors, using all eligible RCTs.Search methodsWe searched CENTRAL (Issue 8, 2016) in the Cochrane Library, MEDLINE (1946 to 31 August 2016), Embase (1980 to week 352016), and CINAHL Plus (1937 to 31 August 2016) on 31 August 2016. We also searched ClinicalTrials.gov on 5 July 2017 and theWorld Health Organization International Clinical Trials Registry Platform (WHO ICTRP) on 6 July 2017. We checked reference listsof relevant articles and applied no language restrictions.Selection criteriaWe selected RCTs assessing the effects of whole grain foods or diets containing whole grains compared to foods or diets with a similarcomposition, over a minimum of 12 weeks, on cardiovascular disease and related risk factors. Eligible for inclusion were healthy adults,those at increased risk of CVD, or those previously diagnosedwith CVD.Data collection and analysisTwo review authors independently selected studies. Data were extracted and quality-checked by one review author and checked bya second review author. A second review author checked the analyses. We assessed treatment effect using mean difference in a fixed-effect model and heterogeneity using the I2statistic and the Chi2test of heterogeneity. We assessed the overall quality of evidence usingGRADE with GRADEpro software.